Analysis of the Patpong multi-story parking garage operation - Byun, Joon-ho; Drew, Donald R.; Jones, John Hugh; Pakorn Adulbhan; Asian Institute of Technology (Bangkok : Asian Institute of Technology, 1973)
A considerable amount of research has been done on parking problems, but most of the studies have been about parking characteristic during peak periods. Emphasis has been placed on the analysis of the whole working day be means of a marcro-simulation. Efforts have also been made to develop formulas for the parking-duration characteristics of drivers in the Patpong district in the Bangkok metropolitan area. Both data collection and analysis of data are essential initial steps in the study of parking characteristics. Data were analyzed to discover the arrival pattern of drivers at the Patpong parking garage. Parking duration was formulated and correlated with field observations to achieve the goal of developing the system model. Finally, the system model was developed to permit experiments to be carried out; validation was obtained by using the Chi-square test.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering at the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1973
Keywords: Parking garages; Automobile parking -- Bangkok